SEM/EDS analyses on shape memory alloy subjected to electrochemical corrosion - Baciu, E R; Vasluianu, R I; Bolat, M; Bulancea, B; Murariu, A; Bosînceanu, D G (IOP conference series. Materials Science and Engineering, 2019)
The aim of the present paper was to investigate the modifications occurred in the Ti-based shape memory alloy subject to electrochemical corrosion in artificial saliva. By 2D and 3D microscopy and by qualitative determinations of the luminous variation we could notice the effects of electrochemical corrosion tests on the surface of the metallic material, and by EDS determinations (Line and Mapping modes) of the surface chemical composition we could determine the chemical modifications produced following the corrosion tests.